SMEs and the environment - Howarth, Richard (Henry Stewart Talks, 2011)
What are SMEs, The 'Need' to Define SMEs, SMEs and the Economy (overview of importance), SMEs and the Environment (identifying the link and importance of SMEs), Overview of SME Environment Literature (affecting and constraints to behaviour), Conceptualising the Situation/Problem and State of the Art of Literature, From Theory to Practice and Back Again